2013
DOI: 10.2109/jcersj2.121.382
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro outcomes of alumina, zirconia and their composited ceramic-on-ceramic hip joints

Abstract: Despite of brittleness, Ceramic-on-Ceramic (CoC) hip joints are appealing to arthritic patients because of its low friction rate, high wear resistance and low risk of osteolysis. The objectives of the study were to review and summarize the performance of Alumina, Zirconia and their functional graded material (FGM) for artificial hip joints in vivo and vitro outcomes. The Method of the study was scoping review which focused on the peer reviewed journals containing with alumina, zirconia and alumina zirconia FGM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…According to the 2014 Canadian Joint Replacement Registry, the numbers of hip and knee replacements have increased by 16.5% and 21.5%, respectively, over the last five years 3 . The demographics include an increasing number of younger patients (45-64 years) and thus, prostheses are now required to last over 30 years [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2014 Canadian Joint Replacement Registry, the numbers of hip and knee replacements have increased by 16.5% and 21.5%, respectively, over the last five years 3 . The demographics include an increasing number of younger patients (45-64 years) and thus, prostheses are now required to last over 30 years [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the Al 2 O 3 induces the activation of human macrophages [ 2 , 3 , 40 ]. In addition, we further found that the systemic injection of Al 2 O 3 FPs promoted the activation of macrophages, Th1, and Tc1 cells, leading to exacerbation of the inflammatory diseases such as colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Alumina ceramic articulation, made of aluminum oxide (Al 2 O 3 ), is one of the bearing surfaces of hip arthroplasty, which is well known to have high resistance to wear and high chemical stability [ 1 , 2 , 3 ]. For these reasons, alumina ceramic articulation has been used for several decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total hip replacement (THR) is a surgical approach that can successfully relieve pain and restore hip joint function . Advances in technology help prosthesis designers and surgeons customize implants and prolong the lifespan of THR .…”
mentioning
confidence: 99%